UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA DENGAN MENGGUNAKAN MEDIA AUDIO VISUAL - Rupina Magdalena Tarigan (JURNAL CURERE, 2018)
This study aims to investigate the implementation of learning by using audio visual media at Thermal Energy and Sound Energy in the fourth grade SDN 060937 Medan Johor in the school year 2016/2017 and determine learning outcomes in Sains lesson after using the Audio Visual Media Highlights Thermal Energy and Sound in fourth grade SDN 060937 Medan Johor in academic year 2016/2017. To achieve such a research study class action. Subjects in this study were students in fourth grade SDN 060937 Medan Johor in academic year 2016/2017 totaling 36 students. The object of this research is the use of audio-visual media in improving student learning outcomes in science subjects in the fourth grade SDN 060937 Medan Johor in to investigate the implementation of student learning.Audio Visual Media is a tool that is used to convey messages / information via voice and images in the learning process. Data collection tool used in this study is the observation sheet and multiple choice test Of the actions performed by using audio-visual media on the test cycle I and cycle II obtained the degree of mastery learning. Implementation of learning obtained an increase where the number of teacher activityobservation in the cycle I 59.58% and 76.66% in the second cycle, the activity of students in the first cycle was obtained 65.45 and the second cycle was obtained 74.54. The results showed in the first cycle of 24 students who pass the KKM (67%) and 12studentdid not pass the KKM (33%). In the second cycle students who who pass the KKM32 people (89%) and 4 students who did notpass the KKM (11%).Based on the results, it can be concluded that the implementation of learning by using audio-visual media on the subject of heat energy and noise in the fourth grade SDN 060937Medan Johor can improve student learning outcomes.